Municipal rating system: A municipality compliance index - Galv\~ao Meirinhos; Maximino Bessa; Carmem Pereira Leal; Rui Silva (Administrative Sciences, 2022)
This research paper presents and discusses the main results generated and obtained with the proprietary computer platform CIDIUS®, developed by the authors of this work, which aims to support the decision-making process of Portuguese mayors. Thus, keeping in mind the theoretical models and based on the data collected through the questionnaire given to the population, we tried to understand the influence that the dimensions Notoriety, Image, and Reputation (NIR), Citizen and Voter Expectations (CVE), Contestation and Complaint of the Municipal Executive (CCME), Perceived Value (PV), and Organizational Performance and Perceived Quality (OPPQ) has a positive effect on Municipe Satisfaction (MS). The parishes of the municipality of Valongo were selected and analyzed, namely the parishes of Alfena, Campo e Sobrado, Valongo, and Ermesinde, and a total of 998 valid questionnaires were collected. It was concluded that all studied dimensions except the Organizational Performance and Perceived Quality (OPPQ) dimension had a positive and statistically significant impact on Municipe Satisfaction (MS). The results of this research suggest the need for the use of these opinion-gathering techniques to encourage active citizen involvement in the daily life of their municipality, as well as the need for valid information that gives executives the ability to take political action that is appropriate to the interests and expectations of citizens.
Keywords: 350; Municipal Rating System; notoriety; reputation; organizational performance; Municipe Satisfaction